Students’ Silence and Minimal Participation in Classroom Discourse: Exploring Students’ Reflections - Dina Melani Zahra; Nafidhatul Maulla; Nanda Nur Chabibah; Reni Oktafia Agustin; Nagita Slavina; Anggita Eka Damayanti; Dewi Puspitasari (Dinamika Bahasa dan Budaya, 2026)
This study investigates students’ reflections on their silence and minimal participation in classroom discourse. The research aims to understand why students tend to stay silent or participate minimally during classroom interactions. Using a qualitative approach, the study involves university students as participants, with data collected through simple reflective interviews. The findings show that students’ silence is influenced by several factors, such as lack of confidence, fear of making mistakes, and limited language ability. Some students also report that classroom atmosphere and teaching style affect their willingness to speak. Through reflection, students become more aware of their passive behaviour and express a desire to participate more actively. Keywords: Student Silence, Student participation, Classroom Discourse, English Learning, Classroom Interaction.